1999
DOI: 10.2337/diabetes.48.10.1995
|View full text |Cite
|
Sign up to set email alerts
|

In vivo prevention of hyperglycemia also prevents glucotoxic effects on PDX-1 and insulin gene expression.

Abstract: Chronic exposure of pancreatic islet beta-cell lines to supraphysiologic glucose concentrations causes defects in insulin gene expression and insulin secretion. To determine whether these in vitro phenomena have pathophysiologic relevance in vivo, we studied the Zucker diabetic fatty (ZDF) rat, an animal model of type 2 diabetes. The ZDF animals had relatively higher levels of glycemia and islet insulin mRNA at 6 weeks of age than age-matched Zucker lean control (ZLC) rats. As glycemia increased in 12- and 16-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
2
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 10 publications
6
59
2
4
Order By: Relevance
“…Excessive cell death through apoptosis or necrosis may contribute to acute organ failure as well as chronic diseases involving the loss of postmitotic cells (44). Several studies in the past decade have shown that chronic elevation of blood glucose concentrations in both humans and experimental animal models leads to ␤-cell dysfunction in terms of insulin secretion and insulin synthesis (45)(46)(47). Both in vivo and in vitro studies on rodent islets have suggested that hyperglycemia is associated with features of apoptosis when the architecture of the islet is maintained (11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive cell death through apoptosis or necrosis may contribute to acute organ failure as well as chronic diseases involving the loss of postmitotic cells (44). Several studies in the past decade have shown that chronic elevation of blood glucose concentrations in both humans and experimental animal models leads to ␤-cell dysfunction in terms of insulin secretion and insulin synthesis (45)(46)(47). Both in vivo and in vitro studies on rodent islets have suggested that hyperglycemia is associated with features of apoptosis when the architecture of the islet is maintained (11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Nomikos et al (22) demonstrated that in vivo treatment with superoxide dismutase and catalase protected islet tissue from oxygen metabolites induced by transplantation of islet allografts. Metformin or troglitazone, both of which have antioxidant properties, prevent hyperglycemia in the ZDF rat (23,24 (29) found that vitamin E failed to restore glucose-induced insulin secretion in rat pancreatic islets transplanted under the kidney capsule in streptozotocininduced diabetic rats. On the other hand, Ihara et al (11), who had previously noted increased immunostaining for 8-OH-deoxyglucose and HNE-modified proteins in GK islets, found that vitamin E had beneficial effects on glycemic control in GK rats, which was accompanied by significant improvement in insulin secretion and lower levels of HbA 1c (30).…”
Section: Evidence That Antioxidant Drugs and Overexpression Of Antioxmentioning
confidence: 99%
“…These findings support chronic oxidative stress as a potential mechanism of action for glucose toxicity and point away from nitric oxide species as a candidate ROS in this animal model. In this context, it is interesting to recall that troglitazone, a drug that prevents glucotoxic decreases in insulin RNA levels in the ZDF animal (23,24), is also an antioxidant. Gene overexpression experiments have been designed to test whether increased levels of antioxidant enzymes in pancreatic islets might protect against oxidative stress.…”
Section: Evidence That Antioxidant Drugs and Overexpression Of Antioxmentioning
confidence: 99%
“…Currently, the reports on the effects of PPAR-␥ on insulin secretion are contradictory. PPAR-␥ agonists can decrease insulin secretion in diabetic animal models, whereas activation of PPAR-␥ does not acutely improve insulin secretion in isolated human islets (Table 1) (4,5,30,(33)(34)(35)(36)(37)(38)(39)(40). However, it is reported that PPAR-␥ agonists can protect the ␤-cells from apoptosis and restore the function of ␤-cells, including GSIS (39,41,42).…”
Section: Role Of Ppar-␥ In the Glucose-sensing Apparatus Of Pancreatimentioning
confidence: 99%
“…53, SUPPLEMENT 1, FEBRUARY 2004 TZDs can prevent glucotoxic effects on PDX-1 expression in diabetic ␤-cells, indirectly resulting in an increase in the expression of GLUT2 and ␤GK (40). Oral administration of TZDs increases the expression of GLUT2 and ␤GK in the ␤-cells of diabetic ZDF rats.…”
Section: S62mentioning
confidence: 99%